Design and Implementation of 6 DOF ROTARIC Robot Using Inverse Kinematics Method - Fransisko Limanuel; Calvin Susanto; Ferry Rippun Gideon Manalu (Jurnal Elektro, 2020)
This paper will discuss the calculation of inverse kinematic which will be used to control the 6-DOF articulated robot. This robot consists of 6 Dynamixel MX-28 smart servo with OpenCM 9.04 microcontroller. The articulated robot has been simplified to 4-DOF because there are no obstacles in the work area and no special movements are required. The calculation method uses the intersection point equation between the ball and the line, so that it can make it easier to determine the point in calculating the kinematic inverse. The experiment is carried out using the desired position as input for the kinematic inverse to produce the angle of each joint. From the angle of each joint obtained, it will be entered into forward kinematic so that the end-effector position will be obtained. The desired position will be compared with the end-effector position, and then how much difference will be calculated. From the experimental results, it was found that the inverse kinematic method which has been inverted by the forward kinematic produces the same final position. Keywords: 6-DOF manipulator, Articulated robot, inverse kinematics and forward kinematics, Dynamixel MX-28, OpenCM 9